Effects of Exercise on S-IGA and URS in Postmenopausal Women - Sloan, C. A.; Engels, H. J.; Fahlman, M. M.; Yarandi, H. E.; Davis, J. E. (International Journal of Sports Medicine, 2013)
32 postmenopausal women were randomized to a 16-week home-based walking program or control group. Before and after the intervention, each subject completed a graded maximal treadmill test to establish VO2max and resting saliva was collected to determine levels of salivary immunoglobulin A. The 16-week walking program resulted in an increase in VO2max (+10.4%; p<0.01). Repeated measures ANOVA revealed a marked increase in the resting secretion rate of salivary immunoglobulin A (+37.4%; p<0.05) in the exercise group following training. Independent of study group, both before and after the intervention, the secretion rate of salivary immunoglobulin A ( − 32.3%) and saliva flow rate (− 29.3%) were reduced following acute maximal exercise (p<0.05). Weekly upper respiratory symptomatology logs revealed that the number of incidences of upper respiratory symptoms throughout the intervention period were the same and the duration per incidence (control: 5.3±1.5 days; exercise: 6.3±2.2 days) were similar between study groups. These findings in postmenopausal women support that the secretion rate of salivary immunoglobulin A and saliva flow rate are reduced immediately following maximal exercise. Moreover, a 16-week moderate intense walking program can increase the secretion of salivary immunoglobulin A without affecting upper respiratory symptomatology.
Keywords: salivary IgA; immunity; postmenopausal; acute exercise; chronic exercise